2012
DOI: 10.1007/s13632-012-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Formation Mechanisms of Welding Defects in Underwater Friction Stir Welded Aluminum Alloy

Abstract: Underwater friction stir welding (FSW) has been demonstrated to be a promising method for strength improvement of heat-treatable aluminum alloy joints. However, when improper welding parameters are utilized, welding defects, such as voids can be produced in the joints, leading to dramatically deteriorated mechanical properties. Thus to obtain high-quality underwater joints, it is necessary to understand the variables that promote the formation of these defects. In this study, the characteristics of welding de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…This flow pattern constitutes the shoulder driven flow. The rest of pin-sheared material not extruded into shoulder concave undergoes circle and upward flow due to the shearing of pin threads (Ref 17,18), and this flow pattern constitutes the pin driven flow, as illustrated in Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…This flow pattern constitutes the shoulder driven flow. The rest of pin-sheared material not extruded into shoulder concave undergoes circle and upward flow due to the shearing of pin threads (Ref 17,18), and this flow pattern constitutes the pin driven flow, as illustrated in Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the HAZ of the joint disappeared, and the strength and hardness were improved. Other studies also indicated that a forced cooling medium is beneficial for improving the mechanical performances of FSW aluminium alloy joints [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not facilitate the detection or estimation of the discontinuity sizes. Zhang et al, (2012) examined the characteristics of discontinuities in underwater friction stir welds and investigated the formation mechanism of the discontinuities. After welding, joints were cross-sectioned perpendicular to the weld direction, and the weld cross-sections were imaged via light microscopy.…”
mentioning
confidence: 99%